2018
DOI: 10.4314/mmj.v30i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences in integrating cervical cancer screening and treatment into HIV services in Zomba Central Hospital, Malawi

Abstract: BackgroundMalawi has the highest rate of cervical cancer globally and cervical cancer is six to eight times more common in women with HIV. HIV programmes provide an ideal setting to integrate cervical cancer screening.MethodsTisungane HIV clinic at Zomba Central Hospital has around 3,700 adult women receiving treatment. In October 2015, a model of integrated cervical cancer screening using visual inspection with acetic acid (VIA) was adopted. All women aged 20 and above in the HIV clinic were asked if they had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 24 publications
7
33
0
Order By: Relevance
“…Among WLHIV (n = 133), the figure was slightly lower with only 91% recurrence free: this is again in line with international findings and supports the need for careful follow-up in this group of women. 39,45,46 Thermal ablation has now been widely adopted within Malawi both within government and non-governmental organization (NGO)-supported screening services and its use is reported in other contexts. 49,47,48 Critically, in 2019, the WHO 43 issued revised guidance for treatment of cervical precancer lesions, for the first time supporting the use of thermal ablation.…”
Section: Thermal Ablationmentioning
confidence: 99%
“…Among WLHIV (n = 133), the figure was slightly lower with only 91% recurrence free: this is again in line with international findings and supports the need for careful follow-up in this group of women. 39,45,46 Thermal ablation has now been widely adopted within Malawi both within government and non-governmental organization (NGO)-supported screening services and its use is reported in other contexts. 49,47,48 Critically, in 2019, the WHO 43 issued revised guidance for treatment of cervical precancer lesions, for the first time supporting the use of thermal ablation.…”
Section: Thermal Ablationmentioning
confidence: 99%
“…Studies from sub-Saharan Africa have recommended integrating cervical cancer screening into other health services, particularly HIV care [ 26 , 47 49 ]. But our analysis, alongside findings from other studies of cervical cancer integration [ 50 , 51 ], suggests that smooth and successful integration will require adequate funding, robust monitoring and referral systems, a sufficient pool of well-trained and available health workers (across cadres, to enable task shifting), and ongoing demand from clients [ 51 55 ]. There may also be hidden “costs” of integration, for example increasing stigma if other services are bundled with HIV treatment [ 53 , 54 ], and providers may need special training in the process of integration (not only each stand-alone service, but the provision of integrated care) as well as appropriate support and accountability for offering comprehensive services [ 54 ].…”
Section: Discussionmentioning
confidence: 77%
“…Two previous studies, which integrated HIV and cervical cancer screening, have been reported in Malawi, both completed in urban and tertiary facilities. 16 17 This practical experience of integration experience of cervical cancer screening may provide valuable lessons for scale-up in rural Malawi.…”
Section: Discussionmentioning
confidence: 98%
“…VIA will be done alongside the introduction of thermo-coagulation, an alternative method of treating cervical pre-malignant lesions, which has been shown to be feasible in other settings in Malawi. 16 24 Additionally, lessons from integration with HIV care will be applied to integration with other services, such as for patients with common chronic NCDs, to maximise access to and uptake of cervical cancer screening services in rural Malawi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation